(3GdEcJaG aj TQM CdaGX GdTaGs - (3YHO GdHGbi YHO GdeLjO Hf YHO Gddg GdbQTj GdjeGfj JGL GdOjf Gdjefi GdeNRej Gdecjs; (3GdbGVj YjGV , YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3hHYO aEfi CeYfJ GdfXQ ai eUfa GdTjN YjGV Hf ehSi GdehSe HGdTaG ahLOJg SaQkG TQa HTQa ef ENJU Hg s
(3BNQgG (B:s
(3GdSGHY hGdKGef djS ajgeG eG jTcd, hGdJGSY hGdYGTQ ajgeG eG jTcd s
(3Vef eLehY s
(3ai cTa GdXfhf (B1054/2 (3CSeGg JdNjU GdEcJaGs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B220 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B45 s
Keywords: (3GdJGQjNs